NLRP3 Inflammasome Contributes to Lipopolysaccharide-induced Depressive-Like Behaviors via Indoleamine 2,3-dioxygenase Induction - Jeon, Seon-A; Lee, Eunju; Hwang, Inhwa; Han, Boyoung; Park, Sangjun; Son, Seunghwan; Yang, Jungmin; Hong, Sujeong; Kim, Chul Hoon; Son, Junghyun; Yu, Je-Wook (OXFORD UNIV PRESS, 2017)
Background: Inflammation may play a significant role in the pathogenesis of depression, although the molecular target for the treatment of inflammation-mediated depressive symptoms remains to be elucidated. Recent studies have implicated the NLRP3 inflammasome in various psychiatric disorders, including depression. However, the underlying mechanism by which NLRP3 inflammasome activation mediates the progression of depressive-like behaviors remains poorly understood. Methods: We examined whether NLRP3 deficiency influenced depressive-like behaviors and cerebral inflammation following systemic administration of lipopolysaccharide in mice. To further assess the contribution of the NLRP3 inflammasome to the progression of depression, we evaluated the effects of NLRP3 signaling on levels of indoleamine 2,3-dioxygenase. Results: Nlrp3-deficient mice exhibited significant attenuation of depressive-like behaviors and cerebral caspase-1 activation in a lipopolysaccharide-induced model of depression. Treatment with the antidepressant amitriptyline failed to block NLRP3-dependent activation of caspase-1, but inhibited lipopolysaccharide- promoted production of interleukin-1 beta mRNA via suppressing NF-kappa B signaling in mouse mixed glial cultures. Interestingly, lipopolysaccharide administration produced NLRP3-dependent increases in indoleamine 2,3-dioxygenase expression and activity of mouse brain. Furthermore, inflammasome-activating stimulations, but not treatment with the inflammasome product interleukin-1 beta, triggered indoleamine 2,3-dioxygenase mRNA induction in mixed glial cells. Conclusions: Our data indicate that the NLRP3 inflammasome is significantly implicated in the progression of systemic inflammation-induced depression. NLRP3-dependent caspase-1 activation produced significant increases in indoleamine 2,3-dioxygenase levels, which may play a significant role in lipopolysaccharide- induced depression. Collectively, our findings suggest that indoleamine 2,3-dioxygenase is a potential downstream mediator of the NLRP3 inflammasome in inflammation-mediated depressive-like behaviors.
Keywords: ACTIVATION; INTERLEUKIN-1-BETA; ANTIDEPRESSANTS; CYTOKINES; RECEPTOR; RELEASE; DISEASE